تقييم جودة مياه الينابيع المائية في بلدية جادو، جبل نفوسة (ليبيا) - زكريا محمد أبومنجي (The Libyan Journal of Science, 2024)
This study evaluated the drinking water quality of spring water in the Jadu municipality, which is located within the cities located on the Nafusa Mountain and is about 190 km south of Tripoli. The study included 3 water springs: Ain Hamed, Ain Timoqat, and Ain Zarqa. 13 chemical elements were measured for the spring water samples and the spring water samples were evaluated in two ways: first, by comparing the chemical elements to the Libyan drinking water standard specifications No. 82 of 2013. The results showed that the water of Ain Hamed and Ain Timoqat springs exceeded the permissible limits, except for the water of Ain Zarqa, which was within the permissible limits of the specifications. A comparison of the results of the chemical analyzes of the targeted spring water for the years 1992 and 2023 was also conducted and showed that the current water quality is deteriorating compared to the past. The second method of evaluation was using the Water Quality Index (WQI) by adopting the weighted arithmetic index method, where this method depended on 11 chemical elements and classified the water quality according to this method that the water of Ain Hamed spring is of poor quality, while the water quality of Ain Timoqat and Ain Zarqa springs is good.